PERAN KEPEMIMPINAN PENDIDIKAN TERHADAP BUDAYA ADMINISTRASI DAN MANAJEMEN KEARSIPAN DI SEKOLAH - Faizatul Ilmi; Ulya Abdillah Ramadhani; Fadilah Aditya; Adirani Nur Azizah; Siswadi (STKIP Subang, 2026)
This study aims to analyze the role of educational leadership in developing an effective administrative culture and improving records management in schools. Educational leadership plays a strategic role in directing, controlling, and developing school administrative systems, including systematic and sustainable records management. The method used is a qualitative approach through library research by reviewing various literature related to educational leadership, administrative culture, and records management. The findings indicate that visionary, participatory, and value-based leadership can foster a disciplined, transparent, and accountable administrative culture. Furthermore, effective leaders contribute to developing technology-based archival systems, enhancing administrative staff competencies, and ensuring sustainable document management. Therefore, the success of records management in schools is highly influenced by the quality of educational leadership. Keywords: educational leadership, administrative culture, records management, school, educational governance